Distributed algorithms for a robust topology using reconfigurable radios wireless sensor networks. (2017) - Wu, Yueshi; Cardei, Mihaela
In traditional wireless sensor networks (WSNs) communicating on a single channel, the data throughput measured at the sink is constrained by radio capability, contentions, and collisions, which increase in the region closer to the sink. Using software defined radio (SDR) technology, the distributed algorithm radio-mode assignment (RMA) is used by sensor nodes to reconfigure their radio according to some predefined radio-modes, such that resulting topology is connected to the sink. This mechanism reduces interference and increases data delivery rate. In this paper, we extend RMA by adding two distributed algorithms to be used in the presence of a primary user. Sensor nodes operating on the same frequency as the primary user will reassign their radio-mode such that the resulting topology does not interfere with the primary user. We analyse the performance of our distributed algorithms using the ns-3 simulator.